Red Cell Distribution Width (RDW) and future risk of arterial cardiovascular diseases - Lappegård, Jostein (UiT The Arctic University of Norway, 2018)
The papers II-IV are not available in Munin. Paper II: Lappegård, J., Ellingsen, T.S., Skjelbakken, T., Mathiesen E.B., Njølstad, I., Wilsgaard, T., … Hansen, J.B. (2016). Red cell distribution width is associated with future risk of incident stroke. Available in Thrombosis and Haemostasis, 115(1), 126-134. Accepted manuscript version available in Munin. Paper III: Lappegård, J., Ellingsen, T.S., Vik, A., Skjelbakken, T., Brox, J., Mathiesen E.B., … Hansen, J.B. (2015). Red cell distribution width and carotid atherosclerosis progression. Available in Thrombosis and Haemostasis, 113(3), 649-654. Accepted manuscript version available in Munin. Paper IV: Lappegård, J., Ellingsen, T.S., Hindberg, K., Mathiesen, E.B., Njølstad, I., Wilsgaard, T., … Hansen, J.B. Impact of chronic inflammation, assessed by hs-CRP, on the association between red cell distribution width and arterial cardiovascular disease: The Tromsø Study. (Manuscript). Myocardial infarction (MI) and stroke rank as the top two killers on the world health organization’s causes of death statistics. Awareness of risk factors is important for targeted prevention of disease, and identification of novel risk factors can further improve the preventive measures. Red cell distribution width (RDW), a measure of the variability in size of the circulating erythrocytes, could be such a risk factor. A growing number of studies are describing a relationship between RDW and arterial CVD. However, study design and study population limited most of these studies. We therefore aimed to investigate the relationship between RDW and MI, stroke and atherosclerosis in a prospective study of initially disease-free subjects, and explore the underlying mechanism for these associations. The study population in this thesis was recruited from the fourth (1994-95) and fifth (2001-02) surveys of the Tromsø Study, a large population-based cohort with >27 000 participants. Information on study participants was collected through physical examinations, blood samples and ...